Smart textiles toward a wearable motion system - Bartalesi, R.; Carbonaro, N.; Lorussi, F.; Tesconi, M.; Tognetti, A.; Zupone, G.; de Rossi, D. (Ninth International Symposium on the 3-D Analysis of Human Movement, June 28-30, 2006, Valenciennes, France, 2006)
This paper presents the development of an innovative measuring system devoted to the human movement analysis using smart textiles that are realized with electrically conductive elastomer composites (CEs). CEs show piezoresistive properties when a deformation is applied and in several applications CEs can be integrated into fabric or other flexible substrate as a strain sensor. Moreover, integrated CE sensors may be used in biomechanical analysis to realize wearable kinesthetic interfaces that are able to detect posture and movement of the human body. Clinical requirements such as comfort, good fit and unobtrusivity are satisfied. Actually, CEs behavior presents some peculiar nonlinear phenomena, requiring a complex treatment of signals.